'Snail factors in testicular germ cell tumours and their regulation by the BMP4 signalling pathway'. (12th June 2020) - Micati, Diana J.; Radhakrishnan, Karthika; Young, Julia C.; Rajpert‐De Meyts, Ewa; Hime, Gary R.; Abud, Helen E.; Loveland, Kate L.
Abstract: Background: Snail transcription factors mediate key cellular transitions in many developmental processes, including spermatogenesis, and their production can be regulated by TGF‐β superfamily signalling. SNAI1 and SNAI2 support many cancers of epithelial origin. Their functional relevance and potential regulation by TGF‐β superfamily ligands in germ cell neoplasia are unknown. Methods: SNAI1, SNAI2 and importin 5 (IPO5; nuclear transporter that selectively mediates BMP signalling) cellular localization was examined in fixed normal adult human and/or neoplastic testes using in situ hybridization and/or immunohistochemistry. SNAI1 and SNAI2 functions were assessed using the well‐characterized human seminoma cell line, TCam‐2. Cell migration, adhesion/proliferation and survival were measured by scratch assay, xCELLigence and flow cytometry following siRNA‐induced reduction of SNAI1 and SNAI2 in TCam‐2 cells. The potential regulation of SNAI1 and SNAI2 in TCam‐2 cells by TGF‐β signalling ligands, activin A and BMP4 was evaluated following 48 hours culture, including with siRNA regulation of IPO5 to selectively restrict BMP4 signalling. Results: In normal testes, SNAI1 transcript was identified in some spermatogonia and in spermatocytes, and SNAI2 protein localized to nuclei of spermatogonia, spermatocytes and round spermatids. In neoplastic testes, both SNAI1 and SNAI2 were detected in GCNIS and in seminoma cells. SNAI1 and SNAI2 reduction in TCam‐2 cells by siRNAs significantly inhibited migration and survival, respectively. Exposure to BMP4, but not activin A, significantly increased SNAI2 ( 18‐fold). IPO5 inhibition by siRNAs decreased BMP4‐induced SNAI2 upregulation ( 5‐fold). Additionally, SNAI2 reduction using siRNAs inhibited BMP4‐induced TCam‐2 cell survival. Conclusions: This is the first evidence that SNAI1 and SNAI2 are involved in human spermatogenesis, with independent functions. These outcomes demonstrate that SNAI1 and SNAI2 inhibition leads to loss of migratory and viability capacities in seminoma cells. These findings show the potential for therapeutic treatments targeting SNAIL or BMP4 signalling for patients with metastatic testicular germ cell tumours.